2021
DOI: 10.1007/s43450-021-00162-5
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids from Siparuna cristata as Potential Inhibitors of SARS-CoV-2 Replication

Abstract: The novel coronavirus SARS-CoV-2 has been affecting the world, causing severe pneumonia and acute respiratory syndrome, leading people to death. Therefore, the search for anti-SARS-CoV-2 compounds is pivotal for public health. Natural products may present sources of bioactive compounds; among them, flavonoids are known in literature for their antiviral activity. Siparuna species are used in Brazilian folk medicine for the treatment of colds and flu. This work describes the isolation of 3,3′,4′-tri-O-methyl-que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 39 publications
0
15
0
1
Order By: Relevance
“…Using Vero E6 and Calu-3 cells, Leal et al recently demonstrated that Siparuna cristata-derived flavonols, 3,7-Di-O-methyl-kaempferol (kumatakenin) and 3,7,3 ,4 -Tetra-O-methyl-quercetin (retusin), inhibited the general viral replication of SARS-CoV-2 with very promising effective concentrations. Kumatakein showed EC50 values of 10 ± 0.7 and 0.3 ± 0.02 µM in Vero and Calu cells, respectively; similarly, retusin also exhibited promise with EC50s of 0.4 ± 0.05 and 0.6 ± 0.06 µM, respectively [140]. This activity was credited to inhibiting the viral 3CLpro and PLpro due to the authors' in silico investigations but was not confirmed experimentally.…”
Section: Flavonoids Against Other Sars-cov-2 Targetsmentioning
confidence: 95%
“…Using Vero E6 and Calu-3 cells, Leal et al recently demonstrated that Siparuna cristata-derived flavonols, 3,7-Di-O-methyl-kaempferol (kumatakenin) and 3,7,3 ,4 -Tetra-O-methyl-quercetin (retusin), inhibited the general viral replication of SARS-CoV-2 with very promising effective concentrations. Kumatakein showed EC50 values of 10 ± 0.7 and 0.3 ± 0.02 µM in Vero and Calu cells, respectively; similarly, retusin also exhibited promise with EC50s of 0.4 ± 0.05 and 0.6 ± 0.06 µM, respectively [140]. This activity was credited to inhibiting the viral 3CLpro and PLpro due to the authors' in silico investigations but was not confirmed experimentally.…”
Section: Flavonoids Against Other Sars-cov-2 Targetsmentioning
confidence: 95%
“…Flavonoids are natural phytochemicals with antiviral properties which have been discovered to inhibit different targets of SARS-CoV [19] such as interfering with S protein and blocking enzymatic activities of viral proteases 3-chymotrypsin like proteases (3CL pro ), papain-like proteases (PL pro ). Previous research suggests that methylated avonoids, such as retusin, could be used as an antiviral or adjuvant medication in the treatment of COVID-19 [20]. Flavonoids are promising plant-derived chemicals for treating SARS-CoV-2 infection, either through direct antiviral effects or by controlling the host immunological response to viral infection [21].…”
Section: Flavonoids and Their Antiviral Potential On Coronavirusmentioning
confidence: 99%
“…On the other hand, studies have observed that flavonoids contribute to the reduction of ROS accumulation decelerates the coronavirusactivated apoptotic signalling (Diniz et al 2020;Godinho et al 2021). In silico molecular docking studies have been performed to evaluate and validate the inhibitory effect of flavonoids based on the hydrogen-bonding distance between selected amino acid residues of the catalytic site from 3CLpro and PLpro SARS-CoV-2 proteases and flavonoids (Leal et al 2021).…”
Section: Flavonoidsmentioning
confidence: 99%